Land use land cover change as a casual factor for climate variability and trends in the Bilate River Basin, Ethiopia. - Samuel Shibeshi Bikeko; Dr E Venkatesham (PLoS ONE)
Land use and land cover (LULC) changes are crucial in influencing regional climate patterns and environmental dynamics. However, the long-term impacts of these changes on climate variability in the Bilate River Basin remain poorly understood. This study examines the spatiotemporal changes in LULC and their influence on climate variability in the Bilate River Basin, Ethiopia, over the period from 1994 to 2024. Utilizing multispectral satellite imagery from Landsat 5, 7, and 8, along with meteorological data from five stations, LULC was classified using the Random Forest algorithm on the Google Earth Engine platform. Climate variability and trends were assessed using the Mann-Kendall trend test, the Standardized Precipitation Index (SPI), and the Standardized Temperature Index (STI). The results reveal a consistent decline in forest cover, with a rapid annual loss of 4,681.2 hectares between 2014 and 2024. Concurrently, agricultural land expanded at an annual rate of approximately 1,141 hectares, while urban areas grew by 24.3 hectares annually in recent years. These LULC changes have contributed to significant climate variability in the region. The upper catchment experienced notable declines in rainfall and warming across all seasons. In the middle catchment, spring rainfall increased, accompanied by moderate summer warming. The lower catchment saw significant increases in spring and autumn rainfall, with no notable temperature trends. These findings highlight the critical impact of LULC changes on the region's climate and emphasize the need for sustainable land management and conservation practices to address deforestation, urbanization, and agricultural expansion.